2006
DOI: 10.1523/jneurosci.1810-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Brain-Derived Neurotrophic Factor Expression and Neurosecretory Function inMecp2Null Mice

Abstract: Disruptions in brain-derived neurotrophic factor (BDNF) expression are proposed to contribute to the molecular pathogenesis of Rett syndrome (RTT), a severe neurological disorder caused by loss-of-function mutations in methyl-CpG-binding protein-2 (MeCP2). Although MeCP2 is a transcriptional regulator of BDNF, it is unknown how MeCP2 mutations affect transynaptic BDNF signaling. Our findings demonstrate an early, abnormal neurosecretory phenotype in MeCP2-deficient neurons characterized by significant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(145 citation statements)
references
References 30 publications
7
133
3
2
Order By: Relevance
“…345 There are also reports that Mecp2 plays a role in the regulation of Bdnf levels. 134,201,202 Reduction in the levels of Bdnf exacerbates the phenotype of both the Rett syndrome-model mouse 346 and the Sert deletion line. [208][209][210] In the Rett syndrome-model mouse, Bdnf overexpression with an inducible Bdnf transgene leads to partial correction of abnormalities linked to loss of Mecp2 function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…345 There are also reports that Mecp2 plays a role in the regulation of Bdnf levels. 134,201,202 Reduction in the levels of Bdnf exacerbates the phenotype of both the Rett syndrome-model mouse 346 and the Sert deletion line. [208][209][210] In the Rett syndrome-model mouse, Bdnf overexpression with an inducible Bdnf transgene leads to partial correction of abnormalities linked to loss of Mecp2 function.…”
Section: Discussionmentioning
confidence: 99%
“…[192][193][194] Work with mouse lines characterized by deficient Bdnf has shown that these trophic effects are important for normal serotonergic neurotransmission. [195][196][197][198][199][200] In addition, several lines of evidence have provided support for a role of Mecp2 in the regulation of activity-dependent transcription of Bdnf, 134,201,202 suggesting that alterations in 5-HT signaling could arise from deficient Mecp2 function, through dysregulation of Bdnf. Bdnf-null mice die soon after birth, but mutants have been developed with conditional disruption of Bdnf, limited to either the prenatal or postnatal period.…”
Section: Autism Candidate Genes and Synaptic Functionmentioning
confidence: 99%
“…Initial attempts to rescue Rett mouse models focused on reversing the putative damage caused by the transcriptional changes observed in the KO animals. KO animals exhibit decreased RNA and protein levels of brain-derived neurotrophic factor (BDNF) (89,121,122). Given the importance of BDNF as a neuronal growth factor, attempts have been made to normalize the levels of BDNF in KO animals genetically and pharmacologically.…”
Section: From Patient To Protein: the Molecular Function Of Mecp2mentioning
confidence: 99%
“…For example, Mecp2 null mice exhibit progressive deficits in BDNF levels after birth (Chang et al, 2006;Wang et al, 2006), and genetic restoration of BDNF in the forebrain improves somatomotor function and extends lifespan (Chang et al, 2006). Moreover, neural structures important for cardiorespiratory control, including the nodose cranial sensory ganglia (NGs) and brainstem, exhibit the earliest and most significant known deficits in BDNF expression in the Mecp2 null mouse brain (Wang et al, 2006). Because BDNF is required for the development of NG and brainstem respiratory neurons, as well as breathing (Katz, 2005), we hypothesize that BDNF deficits contribute to the RTTlike respiratory phenotype of Mecp2 null mice.…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, we examined BDNF expression in NG neurons cultured under depolarizing and nondepolarizing conditions. Because the NG comprises a single neuronal cell type (sensory neurons) and exhibits the Mecp2 null BDNF phenotype in vitro as in vivo (Wang et al, 2006), it provides a simple model for exploring mechanisms that underlie BDNF regulation by MeCP2. Our data indicate that Mecp2 null cells exhibit significantly lower levels of BDNF expression than wild type, under both depolarizing and nondepolarizing conditions.…”
Section: Introductionmentioning
confidence: 99%